SONG “KU JAGA DIRIKU”: PREVENT SEXUAL ABUSE IN CHILDREN - Tampubolon, Masrina Munawarah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Cases of sexual abuse against children have increased by 43% from 2022. Sexual education in early childhood should no longer be considered a taboo. Instead, early childhood sexual education can be an effort that deserves support from various parties. Pekanbaru City as the capital of Riau Province still has cases of sexual violence against children. This problem motivated the service team to carry out community service in the form of sexual education through songs for children at Akramunnas Islamic Kindergarten. The service activity begins with an initial evaluation of body parts. Education is provided with multimedia, children and teachers are invited to sing together. At the end of the activity, a final evaluation was conducted. There is an increase in children's understanding of their body awareness and actions that must be taken if they experience potential sexual abuse. It can be concluded that the song